If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21x = 16x + -7 Reorder the terms: 21x = -7 + 16x Solving 21x = -7 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 21x + -16x = -7 + 16x + -16x Combine like terms: 21x + -16x = 5x 5x = -7 + 16x + -16x Combine like terms: 16x + -16x = 0 5x = -7 + 0 5x = -7 Divide each side by '5'. x = -1.4 Simplifying x = -1.4
| 4.3*t-2.1*t-2.3=7.6 | | [x-6]=10 | | 12x+2=4x+1 | | (2x+39)=(7x+9) | | 8-3*x=17 | | 5x+3yx=10 | | [-4x]=16 | | 9x^4-25x=0 | | 8-3*x=16 | | -7x+3(5x+6)=82 | | 2b=19.6 | | -2(3x-4)+3(5x-1)= | | -5x+7=3x-5 | | 6+3x=8+-14 | | x^5-4x^4-32x^3= | | w+2.75=13.13 | | .24=log(x) | | 4-(x-5)=3(x-11) | | [5x]=10 | | 18-2x=x+19 | | q-1.53=7.04 | | 4.33b=495 | | r+1=7.85 | | 4=-8n | | 13x-3=5x-6 | | 6(x-9)=-30 | | 4.33=495 | | 6+-7=8 | | 16x-3=7x+6 | | 4(36+9y)=-72 | | -7/83/4 | | 4r-6-3=4r-9 |